The Sexual Encounters Questionnaire: A gender-inclusive survey of sexual victimization across the lifespan - Catton, Ashley K H; Dorahy, Martin J (Psychological trauma, 2025)
Despite sexual victimization posing a serious social problem worldwide, inconsistencies in the conceptualization, definition, and measurement of sexual violence mean that many victims are not included in surveys designed to quantify the nature of this problem. The present studies developed, piloted, and finalized a novel survey of victimization, the sexual encounters questionnaire (SEQ), a robust and extensive tool that screens for a range of sexual violation scenarios that can be perpetrated against a victim of any gender and age. Study 1 piloted the original version of the SEQ among 458 students while Study 2 examined the psychometric properties of the SEQ in a sample of 150 students. Study 1 found an overall victimization rate of 76.9%, with 59.8% of men and 80.5% of women being identified as victims. The prevalence and severity of victimization were higher among women than men. Twelve-month prevalence rates ranged from 2.2% to 23.4% depending on the type of violation surveyed with an overall 12-month prevalence of 34.9%. Study 2 found convergent validity with other measures of sexual victimization, and discriminant validity with participants' political orientation and a fear of intimacy measure. The SEQ, with more sensitivity to detect sexual victimization, showed high levels of victimization in students. These results suggest the usefulness of the SEQ as a gender-inclusive screening tool for sexual victimization across the lifespan. (PsycInfo Database Record (c) 2025 APA, all rights reserved).